Metal-free Deamidative Ugi Access to Isoindolinones - Baaziz, Samira; Kerim, Mansour Dolè; Cordier, Marie; Hammal, Lamouri; El Kaïm, Laurent (Synlett, 2018)
A two-step isoindolone synthesis has been achieved by using an Ugi/oxidative vicarious nucleophilic substitution sequence starting from 3-nitrobenzoic acid and aromatic aldehydes. Loss of the amido group was observed as well as a further oxidative process towards hydroxyisoindolone derivatives after prolonged stirring open to the atmosphere.
Keywords: Ugi reaction; 3-nitrobenzoic acid; intramolecular vicarious nucleophilic substitution; isolindolones; air oxidation